From Silver to Cocaine : Latin American Commodity Chains and the Building of the World Economy, 1500-2000 - Frank, Zephyr L., 1970-; Marichal, Carlos; Topik, Steven (Book collections on Project MUSE., 2006)
Examining the commodity chains that have connected producers in Latin America with consumers around the world for 500 years, this work follows a specific commodity from its inception, through its development and transport, to its final destination in the hands of consumers.